(3cJGH GdGYJHGW eef CHj HGdENJdGWs - (3EHQGgje Hf eMeO Hf Ndjd GdnqWnQGoHodSj Ke GdMdHj, CHh GdhaGA, HQgGf GdOjf, pSrHW GHf GdnYnLej , J (B841 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf CeG HYO agPG cJGH LeYJg Ydi UQha GdYLe ai GdGSe hGSe GdCH ai eYQaI ef NdW ai YeQg ef GdKbGJ s
(3BNQgG (B:s
(3ef MOjK Hf OQehf GdChd SeGYgG Ydi GdOHhSi hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP (B- (3YHO GdeMSf Hf MeO GdYHGO s
Keywords: (3GdMOjK h GdeUWdMs